Katrina : a history, 1915-2015 - Horowitz, Andy (Andrew Deutsch) (Harvard University Press, 2020)
The Katrina disaster was not a weather event of summer 2005. It was a disaster a century in the making, a product of lessons learned from previous floods, corporate and government decision making, and the political economy of the United States at large. New Orleans's history is America's history, and Katrina represents America's possible future.